A replication study of the association between the IL12B promoter allele CTCTAA and susceptibility to cerebral malaria in Thai population - Izumi Naka (2018)
Background. Interleukin-12 (IL-12), a heterodimeric cytokine composed of p35 and p40 subunits, has been thought to play an important role in the pathogenesis of malaria. The IL-12p40 subunit is encoded by the IL12B gene. An IL12B promoter allele, CTCTAA, at rs17860508 has been reported to be associated with susceptibility to cerebral malaria in African populations. However, this association has not so far been replicated in non-African populations. Methods. To examine whether the CTCTAA allele is associated with susceptibility to cerebral malaria in Asian populations, 303 Thai patients with Plasmodium falciparum malaria (109 cerebral malaria and 194 mild malaria patients) were genotyped for rs17860508 by PCR-direct sequencing. Results. The CTCTAA allele showed a significant association with susceptibility to cerebral malaria in the Thai population (allelic OR = 1.37; one sided P-value = 0.030). Conclusions. The existence of a significant association between the CTCTAA allele and susceptibility to cerebral malaria was confirmed in Southeast Asian population, which was previously reported in African populations. © 2009 Naka et al; licensee BioMed Central Ltd.